Anti‑fungal study on aqueous and ethanolic leaves extracts of Piper sarmentosum - Ibrahim, Maizatul Akma; Emlee, Aiesyaa Majdiena (Wolters Kluwer - Medknow, 2020)
Piper sarmentosum or “Kaduk” had been utilized for treating human diseases in traditional medicine. Aim and Objectives: Previous studies provided evidence for its therapeutic properties such as antimicrobials, anticholesterolemic, and antioxidant. An antifungal agent is highly important to cure diseases caused by pathogenic fungi. Materials and Method: Thus, the aim of this study is to discover the antifungals activity of P. sarmentosum leaves’ aqueous and ethanolic extracts against four pathogenic fungi, namely Candida albicans, Aspergillus niger, Fusarium verticillioides, and Microsporum gypseum. Result: The yield percentage of the aqueous extract was 17.72%, followed by ethanolic extract with 11.95% of yield. Phytochemical analysis by gas chromatography–mass spectrometer showed the presence of acetic acid, hydrocinnamic acid, oxazole, guanidine, pyranone, benzofuran, β‑asarone, and 1‑pentadecene in aqueous extracts, while it showed the presence of β‑asarone, α‑asarone, myristicin, apiol, isocaryophyllene, 1,1‑dichlorocyclopentane, and 14‑chloro‑1‑tetradecanol in ethanolic extract. Conclusion: The antifungal susceptibility by disc‑diffusion test found that the inhibition growth on F. verticillioides by the aqueous extract occurred at a concentration of 100 mg/mL with an average diameter of 7.3 mm ± 0.06. C. albicans, A. niger, and M. gypseum were shown to be insusceptible to both the extracts.